P1161CUTANEOUS MICROCIRCULATORY DYSFUNCTION IN PERITONEAL DIALYSIS PATIENTS. (6th June 2020) - Williams, Jennifer; Gilchrist, Mark; Fraser, Donald; Strain, David; Shore, Angela
Abstract: Background and Aims: Microvascular impairment is an early step in cardiovascular disease (CVD), the major cause of morbidity and mortality in patients with CKD. Changes in skin microvascular reactivity have been shown to reflect more widespread changes in the systemic and coronary microcirculation. Microvascular function is attenuated by advancing age and conditions that commonly coexist with CKD such as diabetes and hypertension. We investigated whether skin microvascular reactivity is impaired in peritoneal dialysis (PD) patients compared with healthy controls and whether this impairment is independent of comorbidity. Method: Forearm skin vasculature was examined in 27 healthy controls, 27 patients on PD and 27 controls matched to the PD patients for age, gender, diabetes and previous CV events. Microvascular function was assessed using laser Doppler flowmetry in combination with post-occlusive reactive hyperaemia (a test of generalised microvascular function) and iontophoretic application of acetylcholine (ACh) and sodium nitroprusside (SNP) to investigate endothelium dependant and non-endothelium dependant vasodilation respectively. Results: Peak post-occlusive flow was lower in the PD patients than in both the healthy controls and the co-morbidity matched group; 90.45 AU (60.9-128.35) in healthy controls, 73AU (58.8-134.4) in matched controls and 56.95AU (45.1-89.8) in PD patients (p=0.0239 healthy controls versus patients, p=0.0373 matched controls versus patients). SNP-mediated vasodilatation was statistically lower in the PD group compared with healthy controls (p= 0.016), ACh response was lower but did not reach statistical significance (p= 0.076). ACh and SNP-mediated vasodilatation trended towards being lower in PD patients than matched controls but did not reach statistical significance. Conclusion: The PD patients were characterised by a generalised dysfunction of the skin microcirculation compared with healthy controls and controls matched for factors known to affect the microcirculation. This appears to be the result of impaired endothelium dependant and independent vasodilatory mechanisms.